Feeling the past: an emotional reflection on an archive. Issue 1 (1st January 2020) - Larsson, Erika
ABSTRACT: This article looks at the photographic parts of the archive of racial biology in Uppsala, Sweden. This material is approached both through works by Swedish Sámi artist Katarina Pirak Sikku as well as through close engagements with the archive itself and its historical circumstances. In the article, the focus is on affective and emotional relations to the archival photographs and the events of their creation. I argue that Pirak Sikku's profound emotional and physical working through of this material has opened a path for others to engage with this archive beyond only seeing it as a concretisation of a highly problematic and dangerous "scientific" practice. Furthermore, I suggest that examining the emotional, embodied and affective aspects is necessary to achieve further understanding not only of this particular archive, but also of harrowing periods of history in general. Finally, I show how an engagement such as that by Pirak Sikku is able to open up perspectives from which care and inquisitiveness can be seen to triumph over even the deepest injustices.